Scandinavians in Chicago : the origins of white privilege in modern America - Jackson, Erika K., 1978- (University of Illinois Press, 2019)
"Until recently, the study of American ethnic history focused almost entirely on groups who fought for legitimacy, operating under the premise that those with uncontested whiteness required no further study. Yet, just as it is vital to study the history of groups who fought to identify as white, so too is it essential to investigate the process by which those who achieved racial hegemony were able to do so. Scandinavians in Chicago explores ideological, gendered concepts of Nordic whiteness and Scandinavian ethnicity employed by native-born Americans in Chicago during the late nineteenth and early twentieth centuries to construct societal hegemony. The focus of this book advances a more comprehensive understanding of the Scandinavian-American experience by examining the process by which Nordics became the embodiment of whiteness and thus were granted racial privilege. This study's intention is to help bridge the gap in our understandings of white racial identity by analyzing the history of those who benefitted most for a social constructed hierarchy of race in America. As evidenced in the election cycle of 2016, America is a country staunchly divided by economic background, ideological positioning, political beliefs, and racial difference, as well as in our understandings of those differences and how we got to where we are today"--